The Development of Local Handicrafts to Enhance the Self-Reliant Household Economy According to Buddhist Principles In Suan Taeng Subdistrict, Mueang Suphan Buri District - Kraichakr, Orachon; Phrametheevorayān; Raksachom , Maechee Kritsana; Yanakitti, Phramaha Warantorn; Thongoran , Miss Charatluck (Mahachula Academic Journal, 2026)
This research article aimed to achieve three objectives: (1) to examine the problems and needs in the development of local handicrafts in Suan Taeng Subdistrict; (2) to develop local handicrafts in order to enhance a self-reliant household economy based on Buddhist principles; and (3) to evaluate the outcomes of such development. The study employed an action research approach. The research instruments included focus group discussion forms and evaluation forms. The participants consisted of 12 individuals in the focus group discussions and 17 participants in the development activities. Data were collected and implemented according to the action research cycle based on the concept of Gerald Susman. Data were analyzed using content analysis and descriptive statistics, including mean and standard deviation. The research findings revealed that: (1) the problems in developing local handicrafts in Suan Taeng Subdistrict comprised four aspects: (1.1) budget constraints in implementing local handicraft development projects; (1.2) the inability to form occupational groups or community enterprises; (1.3) handicraft products developed through training programs organized by the Suan Taeng Subdistrict Administrative Organization could not be practically marketed; and (1.4) the lack of market channels, resulting in the inability to extend the projects toward income generation. Meanwhile, (2) the needs for the development of local handicrafts comprised two aspects: (2.1) the need for marketing channels; and (2.2) the need to learn handicraft skills in order to increase income. Based on these findings, the research team implemented the development of local handicrafts to enhance a self-reliant household economy according to Buddhist principles by employing the C–A–M Model as a framework. The implementation was conducted from March 6 to April 25, 2026, totaling 51 days in Suan Taeng Subdistrict, Mueang Suphan Buri District, Suphan Buri Province. The model consisted of three main components: (1) Creation (C): This component included two activities:(1) material preparation, involving lectures on techniques for preparing materials for local handicraft production; and (2) product creation, in which villagers were guided to learn and practice making local handicrafts, specifically baskets. (2) Advancement (A): This component included two activities: (1) pricing, involving lectures on price setting and cost calculation along with participatory knowledge exchange; and (2) marketing, involving the sale of local handicraft products through online channels and exhibition booths at the Songkran Festival. The sales results generated a total income of 5,410 baht. Additionally, lectures on sales techniques, live-stream selling, and sales ethics were provided to enhance villagers’ knowledge and understanding of marketing. (3) Management (M): This component included two activities: (1) financial planning, involving lectures on household financial management along with assigned exercises on income–expense accounting and financial planning; and (2) financial knowledge transfer, in which participants were encouraged to disseminate the acquired knowledge to household members in order to promote shared learning. This aimed to build financial resilience and strengthen rational decision-making in expenditure. Finally, the evaluation of the development outcomes indicated that the overall results were at a high level (Mean = 3.79, S.D. = 0.10).